Don't Forget the Children! A Review of the Consequences of Natural Disasters and Epidemics on Childhood Health and Mortality in the Past. (2nd January 2023) - Squires, Kirsty; Hookway, Esme; Márquez-Grant, Nicholas
ABSTRACT: Natural disasters, pandemics, and epidemics have devastating impacts on communities. Poverty, famine, ill health, social isolation, and death are some of the consequences of such events. Transformations in culture, religion, political and economic stability, and other social aspects can also be attributed to catastrophic incidents. Whilst such events have been well documented and studied, little attention has been given to their effect on children. Using osteoarchaeological and historical evidence, this review article explores how children appear to have been affected during, and in the aftermath of, natural disasters and epidemics. A range of cases from Antiquity to the modern day is provided, alongside three focal case studies. This research demonstrates analogies with the present-day where countries face disease outbreaks, droughts, floods, and earthquakes. Ultimately, the findings presented in this paper illustrate the extent to which these events shaped the lives and deaths of children in the past.